Seeking or controlling the truth? An examination of courtroom questioning practices by Canadian lawyers. Issue 4 (20th April 2020) - Lively, Christopher J.; Fallon, Laura; Snook, Brent; Fahmy, Weyam
ABSTRACT: The questioning practices of Canadian lawyers were examined. Courtroom examinations ( N = 91) were coded for the type of utterance, the assumed purpose of the utterance, and the length of utterance. Results showed that approximately one-fifth of all utterances were classified as productive for gathering reliable information (i.e. open-ended, probing); less than one percent of all utterances were open-ended. Direct examinations contained more closed yes/no, probing, and open-ended questions. Cross-examinations contained more leading and clarification questions, and opinions. Moreover, cross- (vs. direct) examinations contained more questions with a 'challenging the witness' purpose. The longest utterances were opinions, followed by multiple and forced-choice questions. The longest answers were in response to open-ended questions, followed by multiple and probing questions. Implications for the truth-seeking function of the judiciary are discussed.